Antioxidant and intestinal anti-inflammatory effects of plant-derived coumarin derivatives - Witaicenis, Aline [UNESP]; Seito, Leonardo Noboru [UNESP]; Chagas, Alexandre da Silveira [UNESP]; Almeida Junior, Luiz Domingues de [UNESP]; Luchini, Ana Carolina [UNESP]; Rodrigues-Orsi, Patricia [UNESP]; Cestari, Silvia Helena [UNESP]; Di Stasi, Luiz Claudio [UNESP] (Elsevier B.V., 2014)
Background: Coumarins, also known as benzopyrones, are plant-derived products with several pharmacological properties, including antioxidant and anti-inflammatory activities. Based on the wide distribution of coumarin derivatives in plant-based foods and beverages in the human diet, our objective was to evaluate both the antioxidant and intestinal anti-inflammatory activities of six coumarin derivatives of plant origin (scopoletin, scoparone, fraxetin, 4-methyl-umbeliferone, esculin and daphnetin) to verify if potential intestinal anti-inflammatory activity was related to antioxidant properties.Methods: Intestinal inflammation was induced by intracolonic instillation of TNBS in rats. The animals were treated with coumarins by oral route. The animals were killed 48 h after colitis induction. The colonic segments were obtained after laparotomy and macroscopic and biochemical parameters (determination of glutathione level and myeloperoxidase and alkaline phosphatase activities) were evaluated. The antioxidant properties of these coumarins were examined by lipid peroxidation and DPPH assays.Results: Treatment with esculin, scoparone and daphnetin produced the best protective effects. All coumarin derivatives showed antioxidant activity in the DPPH assay, while daphnetin and fraxetin also showed antioxidant activity by inhibiting lipid peroxidation. Coumarins, except 4-methyl-umbeliferone, also showed antioxidant activity through the counteraction of glutathione levels or through the inhibition of myeloperoxidase activity.Discussion: The intestinal anti-inflammatory activity of coumarin derivatives were related to their antioxidant properties, suggesting that consumption of coumarins and/or foods rich in coumarin derivatives, particularly daphnetin, esculin and scoparone, could prevent intestinal inflammatory disease. (C) 2013 Elsevier GmbH. All rights reserved.
Keywords: Coumarin derivatives; Antioxidant; Inflammatory bowel disease